Investigating the direct and indirect effects of perceived corporate hypocrisy on turnover intentions. Issue 3 (3rd July 2021) - Goswami, Saheli; Bhaduri, Gargi
ABSTRACT: Perceived corporate hypocrisy, a perception of corporations claiming to have a virtuous character that they do not really possess, is a growing concern for US businesses. The purpose of this study was to investigate the impact of retail employees' perceived corporate hypocrisy (PCH) related to corporations' moral responsibility efforts on their work-related behaviors, namely turnover intentions, mediated by their lack of trust and poor attitude towards the corporation. An online self-reported survey was conducted using 520 adult US retail employees. The study results revealed that PCH positively impacted employee turnover intention, participants' lack of trust in the corporation as well their less favorable attitude towards the same. Also, both lack of trust and less favorable attitude mediated the relation between PCH and turnover intention. The study provides implications for corporations and indicates that given employees are irreplaceable resources to the corporation and can act as creators of competitive advantages, it is essential that corporations take initiatives to align their moral values with those of their employees or risk losing them.